GROUND WATER IN VOJVODINA PROVINCE AS A NATURAL RECOURSES - Škorić, Mićo (Economics of Agriculture, 2009)
Ground water in Vojvodina Province is one of the most important living factor especially in agricultural production. Main sourse for crops is water from freatic water which is near the soil surface. Because of big depth of freatic water at the some localities they don`t have influence to crops. Knowledge of ground water regime is important for land reclamation especially for land drainage and irrigation. It is necessary to make regulary observation and analisis at more caracteristic localities. Adeqate measures in order to provide arrangement of groundwater regime should be carried out.